1973
DOI: 10.1126/science.180.4086.632
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake Prediction: Variation of Seismic Velocities before the San Francisco Earthquake

Abstract: A large precursory change in seismic body-wave velocities occurred before the earthquake in San Fernando, California. The discovery that this change is mainly in the P-wave velocity clearly relates the effect to the phenomenon of dilatancy in fluid-filled rocks. This interpretation is supported by the time-volume relation obtained by combining the present data with the data from previous studies. The duration of the precursor period is proportional to the square of an effective fault dimension, which indicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
108
1

Year Published

1975
1975
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 330 publications
(111 citation statements)
references
References 9 publications
2
108
1
Order By: Relevance
“…Saoarensky [1968] and ,4ggarwal et al [1973] suggested that the main effect was due to an increase in V• during the anomalous period. However, the San Fernando study [Whitcomb et al, 1973] showed that the V•,/V• anomaly was due to a large decrease in Vp and a smaller decrease in V,. This observation combined' with the large spatial extent and time scale of the velocity anomaly for the San Fernando event seemed to give support to the dilatancy-diffusion model as formulated by Nur [1972], Whitcomb et al [1973], and Anderson and Whitcomb [1973a, b].…”
mentioning
confidence: 95%
“…Saoarensky [1968] and ,4ggarwal et al [1973] suggested that the main effect was due to an increase in V• during the anomalous period. However, the San Fernando study [Whitcomb et al, 1973] showed that the V•,/V• anomaly was due to a large decrease in Vp and a smaller decrease in V,. This observation combined' with the large spatial extent and time scale of the velocity anomaly for the San Fernando event seemed to give support to the dilatancy-diffusion model as formulated by Nur [1972], Whitcomb et al [1973], and Anderson and Whitcomb [1973a, b].…”
mentioning
confidence: 95%
“…It is thought recently that positive rock dilat;mcy associated with microcrack opening could explain the reported seismic variation prior to earthquakes [Nur, 1972;Whitcomb et al, 1973;Anderson and Whitcomb, 1973;Aggarwal et al, 1973], and as a consequence, rock dilatancy is considered to be of central importance in the understanding of precursory phenomena associated with earthquakes. When it is viewed in this light, Scholz et al [1973] describe the phenomenon of positive dilatancy in rocks as a physical basis for such possible earthquake precursors as change in seismic velocity ratio, electrical resistivity, radon emission, and geodetic measurements, Beaumont and Berger [1974] computed the effect of dilatancy on the tidal response of the crust, and Whitcomb [1975] examined 3495 ltu AND LIVANOS: BULGING IN UNIAXIAl.LY COMPRESSED GRANITE quantitatively the dependence of vertical geodetic (including leveling, tilt, and geometric measurement relative to a celestial frame of reference), and gravity measurements in relation to dilatancy density change.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon, which is also known as dilatancy-diffusion process (BRACE and ORANGE, 1968), is believed responsible for the observed seismic velocity anomalies preceding the earthquakes (NUR, 1972;WHITCOMB et al, 1973;SCHOLZ et al, 1973). Actual drops in resistivity have been measured preceding earthquakes BARSUKOV (1972) in the Garm region of the U. S. S. R. and by MAZZELLA and MoRRISON (1974) in central California.…”
Section: Introductionmentioning
confidence: 99%
“…Based on observed seismic velocity anomalies (WHITCOMB et al, 1974;KANAMORI and HADLEY, 1975) we have chosen three sites in and around the Los Angeles basin. We are very limited in usable sites because of high cultural noise.…”
Section: Introductionmentioning
confidence: 99%